Endocrine mucin-producing sweat gland carcinoma - newly described skin appendageal tumours - Bakrin, Ikmal Hisyam; Rajaintharan, Sandhya; Tawil, Zahrah; Mahayidin, Hasni (Malaysian Society of Pathologists, 2020)
Introduction: Endocrine mucin-producing sweat gland carcinoma (EMPSGC) is a recently described adnexal tumour with a predilection for the face particularly the eye-lids. Considered to be a precursor lesion of mucinous adenocarcinoma, it may represent part of a morphological spectrum. We described a case of this entity, which we believe is the first case to be reported in Malaysia. Case report: A 59-year-old Chinese male presented with a slow-growing cystic lesion over the left lower lateral canthal region. The lesion became progressively larger and nodular within the last 6 months. Histologically, the lesion is a well-circumscribed intradermal tumour with pushing borders extending into the subcutaneous tissue. The tumour cells were arranged in lobules of solid, papillary and cribriform architecture. The cells displayed uniform, medium-sized, round to oval nuclei with stippled chromatin pattern and ample eosinophilic granular cytoplasm. Intracellular mucin (as highlighted by mucicarmine stain) was observed in areas with focal extracellular mucin seen. Mitotic figures were not particularly impressive. By immunohistochemistry study, the tumour cells expressed ER, PR, CK7, GCDFP-15, mammaglobin and EMA diffusely. Chromogranin A and synaptophysin highlighted a significant number of tumour cells. Discussion: The morphology and immunohistochemical profile similarities between EMPSGC and solid papillary carcinoma of the breast (SPCOTB) makes the former considered as the cutaneous analogue of the latter. In fact, one should rule out the possibility of metastatic SPCOTB before considering the diagnosis of EMPSGC.